The Development Information Technology System Management to Create Competitive Advantage in Print Media Business, Lao PDR - Phachanthavong, Anousone; Saengsupho, Sathaporn; Keawtip, Somkit; Ekiem, Bongkochmas (Trends of Humanities and Social Sciences Research, 2021)
This research aims to study the print media business management in Lao PDR. It also analyzed the system design for the development of print media business management system in Lao PDR. And to evaluate technology for print media business management in Lao PDR to create competitive advantage in the print media business group in Lao PDR. This study is research and development consisting of documentary research and survey research. Information groups are 44 print media operators in Lao PDR. In the process of software development, the research also evaluating the system into 3 dimensions; Unit testing, System testing, and Accepting testing. This is to make sure that the system is will be suitable for business process and management can use this software to improve in term of management. The research findings reveal that; 1. The results of the study of print media business management in Lao PDR, covering the management of customer dimensions, financial management, internal management. The study found that the printing business in Lao PDR, mostly 96.5%, is a small business that starts from a family business. The investment is mainly the family's money and invest in technology around 5-8 million Bath. In the field of operations, most of the operator learn from the actual doing (On the job training), where the owners have knowledge, understand the business process and then transferring that knowledge to employees. In term of internal management, mostly use the method of verbally sending or verbally telling work and then recording work in notebook format. Therefore the owner having problems when needing information or statistic for decision making, tracking the progress of work including the standard of pricing which affects the standard and image of business operations. 2. The results of the design and analysis of system development revealed that printing business in Lao PDR mainly focuses on the use of documents and human resources in operations. Therefore, it creating problem in finding historical data, takes longer time to search for information and sometime documents are lost. The summary of monthly and yearly results requires time to collect data. Therefore, the software system will help facilitates users or printing companies in many ways especially tracking historical data search data in the database system. In addition, the system also has real time calculation, thus increasing the work efficiency of employees and organizations as a whole. The developed system aims for continuous work process from customer order, customer contact, work handling by which person, status in production line (finished or pending) to deliver to customer. Only in the production process, production, contact, production and delivery. The system also able to print out related document in every process, also able to track status of many works at the same time, incase work still not complete the system will show why not complete and operator will input information what is the problem. Once the problem was solved, the operator will update the status and the system will show that the work was completed. 3. The results of the evaluation of the software system in the field of printing business administration showed that user interface design is beautiful, convenient to use in unit testing. There is work flow in system and bugs free. Meanwhile system’s requirement has been tested by computer experts and programmers to analyze the usage in the development process. The system found that experts have analyzed and approved all issues. In addition, 95 percent or more are satisfied with the developed software in acceptance testing by computer students and printing business operators in Lao PDR. From in-depth interviews with printing business operators in the Lao PDR, the developed software plays an important role in creating competitive advantage for printing business companies in Lao PDR especially when analyzing the printing business elements in Lao PDR, the business of the Lao people as well as consumers, languages, personnel and culture in printing business in Lao PDR.